Herb mocktail product innovation to improve the creative economy in Wilayut Village - Ramon Ananda Paryontri; Lely Ika Mariyati; Safia Meilia Sari; Nur Azmi Widyastuti (Universitas Muhammadiyah Magelang, 2022)
Herb products have become people's daily consumption. However, herb products are often considered old-fashioned and conventional accompanied by poor packaging. This happens because of the lack of knowledge and skills of herb medicine business players in developing processed products, packaging, and marketing. The purpose of this activity is to increase the knowledge and skills of the PKK group in making the innovative